EVALUATION OF PADDY STRAW BEDDING FOR CROSSBRED COWS IN WINTER (Indian Journal of Animal Production and Management, 2013)
A study on twenty healthy lactating equal producing crossbred cows for a period of 60 days was conducted to observe the effect of paddy straw as bedding with different thickness during winter season at the dairy farm of Guru Angad Dev Veterinary and Animal Sciences University, Punjab. Twenty lactating crossbred cows of similar health and production status were randomly divided into four groups of five animals each. Paddy straw was spread over the floor to a depth of 10 (T10), 20 (T20) and 30 cm (T30) in three treatment groups against control group (T0) where no bedding was provided. The variations in mean body weight were non significant among groups. The milk production was increased by 3.6-17.1% over control group. Total expenditure on bedding ranged only between Rs 53-185/month/animal. So use of paddy straw as bedding material is an economically viable and eco-friendly option.
Keywords: bedding; crossbred cows; economic; paddy; straw; winter